2021
DOI: 10.1016/j.kint.2020.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule 1 is a novel autoantigen in membranous lupus nephritis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 26 publications
1
103
1
1
Order By: Relevance
“…Neural cell adhesion molecule 1 has been detected in both primary MN and membranous lupus nephritis. 37 Our MS/MS data also confirms the finding of neural cell adhesion molecule 1 in approximately 2%-4% of patients with primary MN and membranous lupus nephritis (unpublished data). Another potential antigen, high temperature requirement protein A1 has also been recently described in MN.…”
Section: Other Potential Mn Antigenssupporting
confidence: 88%
“…Neural cell adhesion molecule 1 has been detected in both primary MN and membranous lupus nephritis. 37 Our MS/MS data also confirms the finding of neural cell adhesion molecule 1 in approximately 2%-4% of patients with primary MN and membranous lupus nephritis (unpublished data). Another potential antigen, high temperature requirement protein A1 has also been recently described in MN.…”
Section: Other Potential Mn Antigenssupporting
confidence: 88%
“…NCAM1, a member of the Ig superfamily of proteins (MW, 120 kDa), was identified by Larsen's group [ 13 ▪▪ ] using the same approach as Sethi et al but in addition they performed protein G immunoprecipitation studies from frozen biopsies. NCAM1 was found to colocalize with IgG within glomerular immune deposits.…”
Section: Neural Cell Adhesion Molecule 1: a ’New’ Antigen Also Associmentioning
confidence: 99%
“…Neuropsychiatric disease occurred in 8/20 (40%) patients possibly related to NCAM1 expression in the central nervous system [ 15 ]. Unexpectedly, it could not be detected in podocytes in normal kidney biopsies or non-NCAM1 membranous nephropathy [ 13 ▪▪ ].…”
Section: Neural Cell Adhesion Molecule 1: a ’New’ Antigen Also Associmentioning
confidence: 99%
“…However, so far, circulating autoantibodies to exostosin1/exostosin2 have not been validated. Caza et al identified neural cell adhesion molecule 1 (NCAM1) as a membranous antigen by mass spectrometry analysis [ 17 ]. Patients with NCAM1-positive IMN were followed to identify whether they developed lupus, which is important in determining whether NCAM1-positive or anti-NCAM1 antibodies can be a precursor to SLE [ 17 ].…”
Section: New Diagnostic Biomarkersmentioning
confidence: 99%
“…Caza et al identified neural cell adhesion molecule 1 (NCAM1) as a membranous antigen by mass spectrometry analysis [ 17 ]. Patients with NCAM1-positive IMN were followed to identify whether they developed lupus, which is important in determining whether NCAM1-positive or anti-NCAM1 antibodies can be a precursor to SLE [ 17 ]. In recent years, increasing attention has been paid to the role of the complement system and its regulatory factors in the pathogenesis of IMN.…”
Section: New Diagnostic Biomarkersmentioning
confidence: 99%